Điều tra hợp chất carotenoit trong một số thực vật của Việt Nam - Bích Ngọc, Hà Thị; Huyền Nga, Trần Thị; Mùi, Nguyễn Văn (VNU Journal of Science: Natural Sciences and Technology; Vol 23 No 2, 2007)
Tóm tắt